Aridland Springs in North America: Ecology and Conservation - Smith, Kate (Ethnobiology Letters, 2012)
Review of Aridland Springs in North America: Ecology and Conservation. Lawrence E. Stevens and Vicky J. Meretsky, editors. 2008. The University of Arizona Press and the Arizona‐Sonora Desert Museum, Tucson.Pp. 406, 4 black‐and‐white photos, 28 illustrations, 38 tables, 8 maps, bibliography. 75.00 (cloth). ISBN 978‐0‐8165‐2645‐1.